2000
DOI: 10.1056/nejm200008243430803
|View full text |Cite
|
Sign up to set email alerts
|

Siblings, Day-Care Attendance, and the Risk of Asthma and Wheezing during Childhood

Abstract: Exposure of young children to older children at home or to other children at day care protects against the development of asthma and frequent wheezing later in childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

35
505
10
37

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 841 publications
(587 citation statements)
references
References 31 publications
35
505
10
37
Order By: Relevance
“…These findings were independent of season of home sampling, the baby's age at the time of the visit, gender, the mother's age, insurance type and several risk factors for infant wheeze including: day care attendance (Ball et al, 2000;Stark et al, 2003), endotoxin levels (Park et al, 2001), maternal smoking during pregnancy (Gold et al, 1999;Lannero et al, 2006) and exposure to environmental tobacco smoke (Strachan and Cook, 1997;Stein et al, 1999). Although ''high'' levels of Aspergillus, Cladosporium, and Acrodontium demonstrated positive associations with wheeze in unadjusted analyses (each P value was r0.05), the odds ratios decreased following the addition of season of visit and other covariables.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…These findings were independent of season of home sampling, the baby's age at the time of the visit, gender, the mother's age, insurance type and several risk factors for infant wheeze including: day care attendance (Ball et al, 2000;Stark et al, 2003), endotoxin levels (Park et al, 2001), maternal smoking during pregnancy (Gold et al, 1999;Lannero et al, 2006) and exposure to environmental tobacco smoke (Strachan and Cook, 1997;Stein et al, 1999). Although ''high'' levels of Aspergillus, Cladosporium, and Acrodontium demonstrated positive associations with wheeze in unadjusted analyses (each P value was r0.05), the odds ratios decreased following the addition of season of visit and other covariables.…”
Section: Discussionmentioning
confidence: 68%
“…These observations could represent exposure to relatively high indoor fungal levels at a young age or exposure to respiratory syncytial virus or rhinovirus at an age when small airway size can be a factor in the development of wheeze during viral infection (Heymann et al, 2004;Sears and Johnston, 2007). Nonetheless, ''high levels'' of Penicillium remained a significant predictor of wheeze even after accounting for the effects of season of mold collection, the age of the baby at the sample collection date and day care attendance, a surrogate measure of respiratory infection during infancy and early childhood (Ball et al, 2000;Stark et al, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Analogously to increased family size, early attendance to day care is considered to reduce the risk for atopic conditions, largely as a result of increased exposure to infections (41,42). A recent review (43), however, showed that the results from the eight studies included in the analysis were highly discrepant, and any conclusions whether there is an (inverse) relationship between day care attendance and asthma and atopy could not be drawn.…”
Section: Family Size and Early Attendance To Day Carementioning
confidence: 99%
“…8 At the univariate level, the stronger risk with having a single bedroom at age 11 than age 8 is similar to a recent report that the age at contact with other children predicts childhood wheezing and asthma. 30 The association of HD risk with having a single bedroom at age 11 in a small childhood household suggests a potent effect of a sequence of socially isolating circumstances throughout childhood. Reasons for the differences in risk patterns between nonwhites and whites are proposed below.…”
mentioning
confidence: 99%